On the foundations of Lévy finance: Equilibrium for a single-agent financial market with jumps - Frederik Herzberg (Bielefeld University, Institute of Mathematical Economics (IMW), 2008)
For a continuous-time financial market with a single agent, we establish equilibrium pricing formulae under the assumption that the dividends follow an exponential Lévy process. The agent is allowed to consume a lump at the terminal date; before, only flow consumption is allowed. The agent's utility function is assumed to be additive, defined via strictly increasing, strictly concave smooth felicity functions which are bounded below (thus, many CRRA and CARA utility functions are included). For technical reasons we require that only pathwise continuous trading strategies are permitted in the demand set. The resulting equilibrium prices depend on the agent's risk-aversion through the felicity functions. It turns out that these prices will be the (stochastic) exponential of a Lévy process essentially only if this process is geometric Brownian motion.
urn:nbn:de:hbz:361-14203
Keywords: 330; Financial equilibrium; Asset pricing; Representative agent models; Lévy processes; Nonstandard analysis; Capital Asset Pricing Model; Stochastischer Prozess; Kapitalmarkttheorie; Theorie